OFR-66(1)-76 Research And Development Program On The Disposal Of Retorted Oil Shale--Paraho Oil Shale Project ? Phase II Interim Report ? I. Introduction ? 1. General (The National Institute for Occupational Safety and Health (NIOSH), 1975)
A PRELIMINARY PROGRAM, dated April 25, 1974, was prepared for Development Engineering, Incorporated (DEI) on research and development laboratory, field and other engineering studies for the disposal of retorted oil-shale materials. This PRELIMINARY PROGRAM included a discussion on the peculiarities of the retorted shale materials to be investigated and a discussion of the various laboratory and field tests which would need to be conducted to define their physical and chemical properties. The PRELIMINARY PROGRAM was divided into eight work phases as follows: I -- Program Development II -- Exploratory laboratory tests on old USBM retorted shale III -- Laboratory tests on pilot plant retorted shale. IV -- Laboratory tests on retorted shale from the semi-works plant and field test plots and ponds. V -- Field compaction tests. VI -- Infiltration pond tests VII -- Bureau of Mines special tests.